The Quality of Life of Elderly Nursing Home Residents and Its Relationship with Different Factors - Aliasquarpoor M; Eybpoosh S (Iran University of Medical Sciences, 2012)
Background & Aims: Aging is a natural phenomenon and a variety of factors including psychological and physical disorders associated with aging has impact on the quality of life of this population .information on factors affecting quality of life of elderly , helps to increase their quality of life. T he aim of this study was to determine the quality of life of seniors and various factors associated with it.   Materials & Methods: It was a descriptive cross-sectional study. Census was used to recruit 164 Kahrizak nursing home residents (Aprill-May2010). Elderlies' quality of life were assessed using LEIPAD questionnair and its associated factors were determined by a researcher made tool . In order to analyze the data, descriptive statistics , chi-square tests and Fisher's exact test were used. To investigate the relationship between individual and environmental factors of quality of life Spearman correlation coefficients was used. Analysis was done using SPSS- PC(v.16). P > 0/05considered as significant.   Results: The quality of life of the highest percentage of subjects was undesirable in the dimensions including physical function (% 43/9) , self care (% 54/9) , social functioning (% 61/6) , sexual functioning (% 89) and life satisfaction (% 62/2). The depression and anxiety dimension of q uality of life in (% 36) of the sample was moderately good and the mental dimension of quality of life of (% 43/3) of the sample was desirable. There were dir ect correlation between physical function , self care, depression and anxiety , and mental function dimensions of quality of life and the personal characteristics and also psychological factors . There were direct relationship between self-care , social functioning , and sexual functioning dimensions of quality of life and before sleep habits. There was also a d irect relationsheep between life satisfaction dimension of quality of life and psychological factors. The findings revealed that there are significant relationnnships among all factors related to the life of elderlies and physical performance (P < 0.01), depression and anxiety (P < 0.01), mental function (P < 0.03) and sexual function (P < 0.00) dimensions of their quality of life. Conclusion: Since the quality of life in this period would be threated by many factors, executing programs to promote social participation, improve medical and consultation services for this population is recommended. More research is needed in this field.